Quantitative Untersuchung der Waldmantelgesellschaften des Haardtrandes zwischen Landau und Bad Durkheim - Abt, Thomas; Frankenberg, Peter; Neff, Christophe (ERDKUNDE, 1993)
Applying cluster analytic methods to the area along the margin of the Haardt Hills, the ubiquitous forest-edge community of Rubo-Prunetum can be subdivided into a richer norther variant and a poorer southern counterpart. Specific spectra of the northern area show a tendency towards thermophilic species of sub-Mediterranean/Eurasian provenance, while mesophilic and more hygrophilic types with sub-oceanic/Central European characteristics are found in the south. The different floristic composition, best described as a domination of Oceanic species in the south and Continental species in the north, seems to be caused by climatic differentiation in the area investigated. Soil analyses and ecological range spectra (according to ELLENBERG) of the specific plant communities show an influence of the substrata, which is also reflected in the cluster analytic pattern. Different mesoclimates presumably determine soil-building processes, which in turn affect the spatial distribution of the vegetation. Due to the importance of such climatic factors, the observed variance of area types cannot be successfully explained without knowledge of climate-dependent meridional soil gradients.